Philippistenia, a new Disteniini genus from the Philippines (Coleoptera: Disteniidae) - Botero, Juan Pablo; Vives, Eduard (Zootaxa, 2021)
A new genus from the Philippines, Philippistenia, is proposed to gather three species previously allocated in Distenia (Distenia) Lepeletier & Audinet-Serville, 1828: Philippistenia heterotarsalis (Heller, 1923) comb. nov.; P. levitemporalis (Heller, 1924) comb. nov.; and P. halconensis (Vives, 2012) comb. nov. Distenia samarensis Villiers, 1959 is proposed as a junior synonym of P. heterotarsalis. Photographs of Philippistenia species are provided. A key to species of the new genus is proposed and the male terminalia are illustrated. Notes on the localization of the type material of Distenia heterotarsalis and Distenia levitemporalis are provided and lectotypes are designated for both species. Additionally, the geographical distribution of the species is expanded.